An Ontology for Product-Service Systems - Annamalai Vasantha, Gokula Vijaykumar; Hussain, Romana; Cakkol, Mehmet; Roy, Rajkumar; Evans, Stephen; Tiwari, Ashutosh (Cranfield University, 2010)
Industries are transforming their business strategy from a product-centric to a more service-centric nature by bundling products and services into integrated solutions to enhance the relationship between their customers. Since Product- Service Systems design research is currently at a rudimentary stage, the development of a robust ontology for this area would be helpful. The advantages of a standardized ontology are that it could help researchers and practitioners to communicate their views without ambiguity and thus encourage the conception and implementation of useful methods and tools. In this paper, an initial structure of a PSS ontology from the design perspective is proposed and evaluated.